Ag-impacts crop yield predictions database - Sosa Arango, Chrystian Camilo; Ramírez Villegas, Julián Armando; Challinor, Andrew J. (2022)
This database represents a compilation of 13980 agronomical yields predictions for main crops worldwide including effects of climate change on them as well as adaptation strategies to mitigate it. The information was extracted from 88 documents (peer-reviewed articles, book chapters, and technical reports). These articles were used in Challinor et al., (2014), available at https://www.nature.com/articles/nclimate2153